SURFACE MOUNT SYSTEMS AND METHODS - THOMPSON, CRAIG (2009)
Herein are disclosed systems and methods and assemblies for mounting an accessory base to a surface (e.g., a wall surface). The systems comprise a mounting bracket which can be attached to the surface by a double-faced adhesive such as a stretch-releasing adhesive. The accessory base can be attached to the mounting bracket. La présente invention concerne des systèmes et des procédés et d'ensembles permettant le montage en surface d'un socle d'accessoires à une surface (par exemple, une surface de paroi). Les systèmes comportent un support de fixation qui peut être fixé à la surface par un adhésif double face tel qu'un adhésif détachable par étirage. Le socle d'accessoires peut être fixé au support de fixation.